2014
DOI: 10.3389/fpsyg.2014.00898
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mother–child interaction quality and child attachment security in at-risk families

Abstract: Child healthy development is largely influenced by parent–child interaction and a secure parent–child attachment is predictively associated with positive outcomes in numerous domains of child development. However, the parent–child relationship can be affected by several psychosocial and socio-demographic risk factors that undermine its quality and in turn play a negative role in short and long term child psychological health. Prevention and intervention programs that support parenting skills in at-risk familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 93 publications
(129 reference statements)
2
52
0
5
Order By: Relevance
“…The relationship between the occurrence of maternal depression symptoms in the postpartum period and child attachment style was evaluated in 28 of the studies included in this review. Of these, 13 found no such relationship [39,[41][42][43][44]46,[56][57][58][61][62][63][64], four studies found a weak influence [35,49,54,60] and 11 found a moderate association [40,45,47,[49][50][51][52]54,58,64]. The studies linked the effects of postnatal depression to a variety of factors.…”
Section: The Influence Of Postnatal Depression On Attachment Stylementioning
confidence: 99%
“…The relationship between the occurrence of maternal depression symptoms in the postpartum period and child attachment style was evaluated in 28 of the studies included in this review. Of these, 13 found no such relationship [39,[41][42][43][44]46,[56][57][58][61][62][63][64], four studies found a weak influence [35,49,54,60] and 11 found a moderate association [40,45,47,[49][50][51][52]54,58,64]. The studies linked the effects of postnatal depression to a variety of factors.…”
Section: The Influence Of Postnatal Depression On Attachment Stylementioning
confidence: 99%
“…There have also been a number of other developments concerning the AQS since the 2004 meta‐analysis. It has continued to be translated into different languages (e.g., De Falco et al, ) and used in a wider range of countries (Posada et al, ). A number of shortened versions of the AQS have been developed (e.g., De Schipper, Stolk, & Schuengel, ), most notably the TAS‐45 (Kirkland, Bimler, Drawneek, McKim, & Schölmerich, ).…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrate higher levels of joy, mutual affection, and humour, and are able to effectively diffuse negative emotions once they appear. The relation between SES and parent-child interactions is typically attributed to discrepancies in available financial (e.g., income, material assets) and human capital (e.g., knowledge, skills) between lowand high-SES families (Coleman, 1988;De Falco et al, 2014;McLoyd & Ceballo, 1998). The current results echo the vast literature supporting the role of SES in children's functioning following TBI, which suggests that higher SES positively influences cognitive, behavioural, social, and emotional recovery following head injury (Anderson, Catroppa, Haritou, Morse, & Rosenfeld, 2005;Crowe et al, 2012;Gerring & Wade, 2012;Holland & Schmidt, 2015).…”
Section: Discussionmentioning
confidence: 99%